2019
DOI: 10.1002/asi.24251
|View full text |Cite
|
Sign up to set email alerts
|

Global village or virtual balkans? evolution and performance of scientific collaboration in the information age

Abstract: Scientific collaboration is essential and almost imperative in modern science. However, collaboration may be difficult to achieve because of 2 major barriers: geographic distance and social divides. It is predicted that the advancement of information communication technologies (ICTs) will bring a puzzled conclusion for collaboration in the scientific community: the “Global Village” trend with significantly increased physical distance among collaborated scientists and the “Virtual Balkans” trend with significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 55 publications
0
15
0
1
Order By: Relevance
“…Owing to the development of the Internet, COVID-19-related information spread quickly around the world. Although the internet provides powerful channels for real-time information sharing over geographic barriers ( Yao, Zhang, Qu & Tan, 2020 ), the dark side of this enhanced connectivity has been revealed in the fact that it at least partially contributed to an escalation in the devastating global effects of the disease, a situation that has been called an “infodemic” ( Zarocostas, 2020 ). An infodemic, which is characterized by false news, misinformation, and conspiracy theories, imposes extra uncertainties and threats on people's daily lives.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the development of the Internet, COVID-19-related information spread quickly around the world. Although the internet provides powerful channels for real-time information sharing over geographic barriers ( Yao, Zhang, Qu & Tan, 2020 ), the dark side of this enhanced connectivity has been revealed in the fact that it at least partially contributed to an escalation in the devastating global effects of the disease, a situation that has been called an “infodemic” ( Zarocostas, 2020 ). An infodemic, which is characterized by false news, misinformation, and conspiracy theories, imposes extra uncertainties and threats on people's daily lives.…”
Section: Introductionmentioning
confidence: 99%
“…Ribeiro et al (2018) argued that international collaboration has been increasing faster than an exponential growth, based on the analysis of over 10 million articles indexed in the Web of Science (Ribeiro et al, 2018). International collaborations bring together researchers from different countries working for common goals by sharing knowledge, resources, and experience, which can enhance academic impact, inspire novel ideas, and carve out successful career paths for scholars (Wagner et al, 2019 ; Yao et al, 2020 ; Zhang et al, 2018 ). For example, Wagner et al ( 2017 ) demonstrated that the number of collaboration countries per paper has significant positive correlation with higher citation counts by examining international collaboration in six traditional disciplines (i.e., engineering, mathematic, astrophysics, virology, agriculture, and seismology).…”
Section: Introductionmentioning
confidence: 99%
“…Much of recent studies have endeavored to identify the determinants affecting international collaboration in several research fields, which can be summarized into four categories, including geographic distance (Abramo et al, 2020 ; He et al, 2020 ; Hoekman et al, 2010 ; Parreira et al, 2017 ; Sidone et al, 2017 ; Yao et al, 2020 ), economic distance (Acosta et al, 2011 ; Fernández et al, 2016 ; He et al, 2021a , 2021b ; Jiang et al, 2018 ; Ni & An, 2018 ), cultural distance (Cassi et al, 2015 ; Choi et al, 2015 ; Gervedink Nijhuis et al, 2012 ; Gui et al, 2019 ; Hoekman et al, 2010 ; Hung, 2008 ; Jiang et al, 2018 ; Plotnikova & Rake, 2014 ), and academic distance (Fernández et al, 2016 ; Kwiek, 2015 ; Osiek et al, 2009 ; Parreira et al, 2017 ). These determinants have been together or individually examined in limited disciplines, and their performance was different because of the underlying differences in disciplines.…”
Section: Introductionmentioning
confidence: 99%
“…Team collaboration is defined as the process where researchers from various affiliations working together for common goals by sharing knowledges, resources and experiences [ 1 ]. It has recently become imperative in the field of artificial intelligence (AI) for serving humanity in more complicate situations.…”
Section: Introductionmentioning
confidence: 99%